2017
DOI: 10.1136/bmjopen-2016-014576
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled non-inferiority trial of primary care-based facilitated access to an alcohol reduction website

Abstract: BackgroundBrief interventions (BIs) delivered in primary care have been shown to be effective in reducing risky drinking, but implementation is limited. Facilitated access to a digital application offers a novel alternative to face-to-face intervention, but its relative effectiveness is unknown.MethodsPrimary care-based, non-inferiority, randomised controlled trial comparing general practitioner (GP) facilitated access to an interactive alcohol reduction website (FA) with face-to-face BI for risky drinking. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 30 publications
1
17
1
Order By: Relevance
“…PNF interventions are mostly used in young people, but less evidence is available for adults with more harmful drinking patterns. For this reason, the study by Johnson et al [25] recruited 837 problem drinkers (9 5 and G 9 on the Alcohol Use Disorders Identification Test [22] (AUDIT)) from a hospital outpatient setting and compared the PNF group with an AO condition. No significant between-group differences were found.…”
Section: Personalized Normative Feedbackmentioning
confidence: 99%
See 1 more Smart Citation
“…PNF interventions are mostly used in young people, but less evidence is available for adults with more harmful drinking patterns. For this reason, the study by Johnson et al [25] recruited 837 problem drinkers (9 5 and G 9 on the Alcohol Use Disorders Identification Test [22] (AUDIT)) from a hospital outpatient setting and compared the PNF group with an AO condition. No significant between-group differences were found.…”
Section: Personalized Normative Feedbackmentioning
confidence: 99%
“…However, no definite conclusions could be reached due to the small sample sizes of those studies. For this reason, Wallace et al [25] recruited 763 adult problem drinkers (≥ 8 on the AUDIT) from primary care during a visit to their GP and randomized them to unguided internet-based BI or to GP-delivered FTF BI. The unguided internet-based BI was significantly more effective (10% reduction) in reducing the number of patients with an AUDIT score ≥ 8, compared to the FTF BI condition (15% increase).…”
Section: Brief Interventionsmentioning
confidence: 99%
“…Patient numbers and loss to follow-up for the trial are reported in figure 1 . Further patient demographics can be found in the main trial findings paper 11 .…”
Section: Resultsmentioning
confidence: 99%
“…Cases of hazardous or harmful drinking prevented at 12 months have been calculated using the data from the main paper for the trial using AUDIT-10 data at 12 months. 11 This was converted to cases prevented per 1000 patients by calculating the percentage of patients that are hazardous or harmful drinkers at 12 months in the face-to-face BI, changing this to a rate per 1000 patient years and applying the OR reported in the main clinical paper 11 for 12 months.…”
Section: Methodsmentioning
confidence: 99%
“…Most internet studies so far have involved hazardous drinkers in student-or general populations (17). Internet-based approaches have shown similar efficacy as face-to-face treatment (18).Webbased advice to reduce drinking among hazardous drinkers has been successfully implemented in PC in a project in Italy (19).…”
Section: Introductionmentioning
confidence: 99%